Scor Quality Model Affecting Manufacturing Firm’s Supply Chain Quality Performance And The Moderating Effect Of Qms - Lam, Kok Hoong (2012)

(untitled)
The main objective of this study is hypothesis testing to explain the nature of the relationship between the independent variables (The SCOR quality model) and the dependent variable (Supply Chain Quality Performance) and moderated by (QMS).